1989
DOI: 10.1177/073428298900700408
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Draw a Person: A Quantitative Scoring System with the WISC-R

Abstract: This study examined the relationship between the Draw A Person: A Quantitative Scoring System and the WISC-R with a referred school-aged population. The significance of difference between the standard scores that the two tests yield was examined, as well as the convergent and concurrent validity of the Draw A Person. Additionally, the differences between specific pairs of scores (e.g., PIQ vs. DAP) required for significance when interpreting results for an individual subject were computed. Results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
10
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
7
10
0
Order By: Relevance
“…When the analysis was conducted without controlling for sex, r  = 0.30, p  = 0.002. The magnitude of this partial correlation is slightly lower than the correlations between 6- to 11-year-old children's scores on the DAP:IQ and the WISC-III that are reported in the DAP:IQ manual [11], but it is consistent with previous studies which have typically found modest to moderate correlations between children's standard scores on earlier versions of HFD tests of intelligence (e.g., DAP:QSS) and the Wechsler tests [10], [26], [27], [28], [29], [31], [32], [33], [34], [45].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…When the analysis was conducted without controlling for sex, r  = 0.30, p  = 0.002. The magnitude of this partial correlation is slightly lower than the correlations between 6- to 11-year-old children's scores on the DAP:IQ and the WISC-III that are reported in the DAP:IQ manual [11], but it is consistent with previous studies which have typically found modest to moderate correlations between children's standard scores on earlier versions of HFD tests of intelligence (e.g., DAP:QSS) and the Wechsler tests [10], [26], [27], [28], [29], [31], [32], [33], [34], [45].…”
Section: Resultssupporting
confidence: 88%
“…Taken together, these findings suggest that the DAP:IQ is a highly reliable measure, however, its correlations to other measures of intelligence are moderate at best. Similar findings have been reported for previous HFD tests such as the DAMT [26], GHDT [26], [27], [28], [29], [30], [31], and the DAP:QSS [10], [21], [28], [32], [33], [34].…”
Section: Introductionsupporting
confidence: 89%
“…The relationship between the DAP:QSS and measures of intelligence and academic functioning has been reported in previous research (Naglieri, 1988;Prewett, Bardos, & Naglieri, 1988, 1989Wisniewski & Naglieri, 1989). The results of these studies provide initial support for using the DAP:QSS as a screening measure of cognitive abilities.…”
supporting
confidence: 78%
“…In addition, Prewett and colleagues (1989) reported correlation coefficients ranging from .34 to .41 between the DAP:QSS and the Kaufman Test of Educational Achievement-Comprehensive Form (KTEA) (Kaufman & Kaufman, 1985) for developmentally handicapped (DH) children. Similar correlations have been reported for the DAP:QSS when compared with the Verbal, Performance, and Full Scale scores of the Wechsler Intelligence Scale for Children-Revised (WISC-R) (Wechsler, 1974) and the Wechsler Intelligence Scale for Children-III (WISC-III) (Wechsler, 1991); correlation coefficients ranged from .29 to .55 (Abell, Wood, & Liebman, 2001;Wisniewski & Naglieri, 1989).…”
Section: Introductionsupporting
confidence: 69%